CARTERS ; QUALITY OF SHARIA BANKING SERVICES - Willy Yusnandar (Proceeding International Seminar of Islamic Studies, 2022)
The development of financial institutions, especially banking, continues to experience a significant increase, this can be seen from the many banking offices that have sprung up around the community. To continue to exist in the banking world, of course, financial institution companies must maintain the quality of their services, of course, this is done so that people feel comfortable with what the bank has. This article will discuss the quality of banking services using the CARTER system, where this dimension has components that can measure the quality of services in banking, it's just that the CARTER system is rarely known by the public, for that the author will describe how to assess service quality by using the CARTER system, which of course anyone can judge about the quality of services in banking